Antibacterial and photo dye degradative ability of copper oxide nanoparticles from Pleurotus cystidiosus - Kamakshi S; Anantha Lakshmi P; Shenbhagaraman R; Jenavio Maria Amirtham P; Siva R; Lakshmanan G; Selvakumari J (Nano Express, 2024)
The present study deals with in vitro experiments for to develop synthesized copper oxide nanoparticles using Pleurotus cystidiosus. Mushroom-based nanoparticles, such as copper nanoparticles have become more significant because of potential biocatalytic properties, including antibacterial activity. The blue-to-brown color shift suggests CuONPs, as confirmed by absorbance maxima at 246 nm in ultraviolet spectroscopy. FTIR spectra reveal the existence of carboxyl, alcohol, and aldehyde carbon; the amine group represents the myco-synthesized copper nanoparticle. Scanning electron microscopy (SEM) nanoparticles show spherical to oval nano aggregates of 80–110 nm in size. The EDX spectrum confirms the presence of Cu at 8.00 keV in myco-synthesized copper oxide nanoparticles. The antimicrobial efficacy of produced copper oxide nanoparticles on human pathogens showed a maximum zone of inhibition against coliform bacteria such as Enterococcus faecalis (32 ± 2), Enterobacter aerogenes (30 ± 1), E. coli (28 ± 1) and least zone of inhibition about 25 ± 1 mm recorded in Streptococcus mutans . The photocatalytic activity of Congo red dye, Malachite green dye, and Remazol blue dye by copper oxide nanoparticles from Pleurotus cystidiosus was investigated, and the results showed a maximum degradation efficiency of 99.2% in Congo red within 90 min. However, moderate degradation was noted in malachite green, and Remazol blue dye has a low degradation efficiency. Thus, myco-synthesized copper oxide nanoparticles from Pleurotus cystidiosus have potent antimicrobial and photocatalytic dye degradation efficacy.